2004
DOI: 10.1124/jpet.104.068031
|View full text |Cite
|
Sign up to set email alerts
|

The Modulating Role of Nuclear Factor-κB in the Action of α7-Nicotinic Acetylcholine Receptor and Cross-Talk between 5-Lipoxygenase and Cyclooxygenase-2 in Colon Cancer Growth Induced by 4-(N-Methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone

Abstract: ABSTRACT4-(N-Methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone (NNK), the tobacco-specific nitrosamine, induces lung cancer in all animal species tested and is thought to contribute significantly to the high lung cancer burden associated with smoking. However, there is no report whether NNK could promote colon cancer growth. To address this hypothesis and the possible signaling pathways involved, we used SW1116 colon cancer cell line to study these biological events in vitro. Results showed that NNK, after 5-h tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 29 publications
(21 reference statements)
3
39
0
Order By: Relevance
“…The TSNA, NNK, has recently been shown to activate NF-jB in normal human bronchial epithelial cells 38 and lung cancer cells 39 as well as colon cancer cells. 40 Herein we showed that NNK treatment of OPL cells and oral cancer cells showed NF-jB activation (as evident from increased levels of NF-jB in the nuclear fraction) and increase in the levels of inflammation related protein COX-2. Our data suggest that NNK is 1 of the carcinogenic components of STE (khaini) that activates NF-jB and its downstream target, COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…The TSNA, NNK, has recently been shown to activate NF-jB in normal human bronchial epithelial cells 38 and lung cancer cells 39 as well as colon cancer cells. 40 Herein we showed that NNK treatment of OPL cells and oral cancer cells showed NF-jB activation (as evident from increased levels of NF-jB in the nuclear fraction) and increase in the levels of inflammation related protein COX-2. Our data suggest that NNK is 1 of the carcinogenic components of STE (khaini) that activates NF-jB and its downstream target, COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…The role for NF-κB in mediating nicotine-dependent decrease of apoptosis has been demonstrated in lung cancer cells (Tsurutani et al, 2005). Nitrosamines stimulate normal human bronchial cell proliferation through activation of the NF-κB (Ho et al, 2005), and promote colon cancer growth in vitro via NF-κB that conveys the biological effect of α7-nAChR (Ye et al, 2004). Therefore, transcriptional and posttranscriptional activation of this signal transduction effector in oral KCs may play a key role in the pathogenesis of head and neck cancer by acting as tumor promoters that facilitate the outgrowth of cells with genetic damage.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that α7 nAChR is essential for a sustained turnover of the mucocutaneous epithelium in humans (Arredondo et al, 2002). The α7 nAChR is also expressed in human cancer cells, and its activation accelerates tumors progression, suggesting that the α7 nAChR-coupled signaling may play an important role in the development of tobacco-related cancers (Ehrhardt et al, 2003;Plummer et al, 2005;Ye et al, 2004). The α7 subunit is first expressed on the cell surfaces of oral keratinocytes (KCs) comprising the lower third portion of the gingival epithelium, and becomes abundant at the terminal stage of cell development in the gingival epithelium (Nguyen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the constitutive NF-κB activation in some HER-2/neu positive breast cancer is a frequent genetic condition (4)(5)(6)(7) and it has been demonstrated that nicotine has a proliferative role on cancer cells through the PI3K/AKT pathway activation and the PTEN pathway inhibition (8,9), we may suppose that the potential role of nicotine in inducing resistance to trastuzumab therapy in MBC is overcome by other predominant molecular and/or genetic mechanisms conditioning the proliferation and invasive processes of cancer in the metastatic phase. With the same rational, the adjuvant setting of breast cancer appears to represent the best setting to analyse the potential detrimental effects of nicotine in trastuzumab based adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Infact, preliminary results also revealed that specific inhibitors of NF-κB and the EGFR family of cell surface receptors in combinations have demonstrated to block proliferation synergistically at concentrations which are ineffective when used individually (6). Preclinical data revealed that 4-(N-Methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone (NNK), the tobacco-specific nitrosamine, was able to stimulate the proliferation of SW1116 colon cancer cell line enhancing NF-κB DNA binding activity (7). Moreover, nicotine, the major alcaloid in tobacco, increases the oxidative stress of colon cancer cells, leading to the activation of NF-κB, a redox-sensitive trascription factor (8) and promotes colon cancer cell proliferation and tumor growth in a dose-dependent manner, increasing EGFR phosphorylation levels (9).…”
Section: Introductionmentioning
confidence: 99%